Islamic Banking - Mirakhor, Abbas; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 1991)
Islamic banks are prohibited from charging or paying interest, and thus can operate only on the basis of profit-sharing arrangements. This paper provides a brief survey of the theory and practice of Islamic banking. It covers developments in Islamic banking since the mid-1970s, how such banks operate, and the analytical underpinnings of a financial system based on Islamic principles. Finally, the future of Islamic banking is assessed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Iran, Islamic Republic of